1998
DOI: 10.3354/meps162265
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fluctuations in cod and pollack along the Norwegian Skagerrak coast

Abstract: We tested whether the long-term fluctuations in abundance of 0-group cod Gadus morhua and pollack Pollachius pollachius sampled from 1919 to 1994 at 38 stations along the Norwegian Skagerrak coast might be related to the North Atlantic Oscillation (NAO). The short-and long-term fluctuations of both species exhibited different spatial structures and were probably of different origins. The former, which were previously shown to be related to biotic interactions, displayed signif~cant highest similarities across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 16 publications
1
60
0
1
Order By: Relevance
“…The occurrence of warm winters over much of Europe during the late 1980s and early 1990s was associated with anomalously low pressures in the region of the Icelandic Low and with pressures higher than normal at lower latitudes, corresponding to a high positive NAO index (Hurrell 1995). There is growing evidence that the abundances of aquatic and terrestrial species were influenced by the NAO (Fromentin and Planque 1996;Fromentin et al 1998;Kröncke et al 1998;Post and Stenseth 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of warm winters over much of Europe during the late 1980s and early 1990s was associated with anomalously low pressures in the region of the Icelandic Low and with pressures higher than normal at lower latitudes, corresponding to a high positive NAO index (Hurrell 1995). There is growing evidence that the abundances of aquatic and terrestrial species were influenced by the NAO (Fromentin and Planque 1996;Fromentin et al 1998;Kröncke et al 1998;Post and Stenseth 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial sigmoid-like temporal trend is observed in most of the time-series (¢gure 2; see Fromentin et al 1997Fromentin et al , 1998. We have nevertheless chosen to perform our analysis without doing any form of detrending since moving average terms may contribute signi¢cantly to low-frequency £uctuations (BjÖrnstad et al 1999a;see Priestley (1981) for a general discussion).…”
Section: (C) Testing the Predictionsmentioning
confidence: 99%
“…SAS Institute 1990, Proc Model;Pindyck & Rubinfeld 1991). The mean c j , is allowed to vary between the series whereas the autoregressive coe¤cients (ar i , i 1, 2, 3) and the moving average term (ma 1 ) are assumed to be the same for all 54 stations; the global trend is incorporated though a thirdorder polynomial in time (poly(t,3)) (Fromentin et al 1997(Fromentin et al , 1998.…”
Section: (C) Testing the Predictionsmentioning
confidence: 99%
“…However, Kornilovs et al (2001) postulate that the observed decline has had, at least in part, an environmental basis in reduced food supply (Calanus). In contrast, Fromentin et al (1998) examine the historic record in the Skagerrak and suggest no relation of cod populations to Calanus, whose abundance cycles with the North Atlantic oscillation. Rather, Fromentin et al (1998) relate changes in cod stocks to changes in amount of area of Zostera available for settlement of the larvae -in other words, a space limitation for juveniles.…”
Section: Crashing Cod Fisheriesmentioning
confidence: 99%
“…In contrast, Fromentin et al (1998) examine the historic record in the Skagerrak and suggest no relation of cod populations to Calanus, whose abundance cycles with the North Atlantic oscillation. Rather, Fromentin et al (1998) relate changes in cod stocks to changes in amount of area of Zostera available for settlement of the larvae -in other words, a space limitation for juveniles. While no simple answer seems to be in sight, the potential influence of environmental variables cannot be discounted.…”
Section: Crashing Cod Fisheriesmentioning
confidence: 99%